Kebijakan Pendidikan Islam di Era Orde Lama dan Orde Baru - Anjasari, Titi (Universitas Muhammadiyah Yogyakarta, 2022)
Islamic education has an important role in life as it relates to moral, socio-cultural and religious values. In the early days of independence until the emergence of the old order and the new order, Islamic education experienced significant development and became a concern from the government so that we can feel the impact at this time. The purpose of this writing is so that readers can understand how islamic education policy in the era of the Old Order and the New Order. The method used in this writing is the study of libraries by taking literature from books, journals through google scholar and related news. The results showed that Islamic education in the Old Order era began to be considered as evidenced by the start of religious education in domestic and private schools but parents and students could refuse if they felt objected. Islamic education in the New Order era began to increase, namely the use of the national curriculum in madrassas such as schools in general.